2002
DOI: 10.1046/j.1464-5491.2002.00631.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of cigarette smoking on soluble adhesion molecules in middle‐aged patients with Type 2 diabetes mellitus

Abstract: Our present study shows that levels of adhesion molecules were higher in diabetic smokers than diabetic non-smokers or non-diabetic smokers, and that cessation after chronic smoking did not restore the levels of sICAM-1 and sE-selectin, though sP-selectin levels were restored. These data suggest a possible mechanism for accelerated atherosclerosis induced by smoking in patients with diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
25
0
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 49 publications
(64 reference statements)
0
25
0
1
Order By: Relevance
“…Moreover, a close relationship between increased urinary albumin excretion, endothelial dysfunction, and inflammation and death risk in diabetic patients has been described [34]. On the other hand, diabetic patients who were smokers had higher concentrations of E-selectin, ICAM-1 and VCAM-1 than non-smokers as has been shown in one report [7].…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…Moreover, a close relationship between increased urinary albumin excretion, endothelial dysfunction, and inflammation and death risk in diabetic patients has been described [34]. On the other hand, diabetic patients who were smokers had higher concentrations of E-selectin, ICAM-1 and VCAM-1 than non-smokers as has been shown in one report [7].…”
Section: Discussionmentioning
confidence: 84%
“…Several studies of the biomarkers of endothelial dysfunction have been done in patients with diabetes mellitus or insulin resistance. Although most of them have demonstrated an increased concentration of E-selectin, P-selectin, ICAM-1 and VCAM-1, there is a broad heterogeneity in the results; mainly in regard to which factor is more highly altered [2,7,[9][10][11][12]. Furthermore, the results in patients with impaired glucose tolerance are discordant [8,12] and some studies have described, in the general population, an increased risk of diabetes mellitus in people with higher biomarkers of endothelial dysfunction [2,13,29,30].…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…P-selectin, which is induced by platelet activation, acts on the adhesion of white blood cells to endothelial cells in the early phase of inflammatory process. In addition, it has been reported that the plasma concentrations of P-selectin in smokers were higher than those of non-smokers [5]. Smoking also induces atherosclerosis through induction of oxidative stress and subsequent elevation of oxidized LDL [6].…”
Section: Introductionmentioning
confidence: 97%
“…[9] E-selectin is a leukocyte adhesion molecule specific to endothelial cells, and soluble E-selectin is a marker of endothelial activation. [10][11][12][13] It may reflect a variety of pathophysiological conditions related to inflammation.…”
mentioning
confidence: 99%